The first investigation of AAC(6’)-Ib enzyme in carbapenem-resistant enterobacteriaceae isolated from Indonesian patients - Beauty Novianty; Ella Amalia; Ziske Maritska; Yuwono; Lusia Hayati (Acta Biochimica Indonesiana, 2019)
Background: Over the past decade, numbers of Carbapenemase Producing-Carbapenem Resistant Enterobacteriaceae (CP-CRE) has been increasing worldwide and it has been becoming a threat because of its resistance against carbapenem which is considered as the “last resort” antibiotic. Therapy options for its infection are still limited. Aminoglycoside serves as one of the most commonly used antibiotics, but the resistance against it has already been presented for a long time. Aminoglycoside Modifying Enzyme (AME) is the most important resistance mechanism against aminoglycoside. AAC(6’)-Ib enzyme is one of the most common AME produced by the gram-negative bacteria. Objectives: This study wished to identify the gene of this enzyme among CRE isolated from infected Indonesian patients in Dr. Mohammad Hoesin Hospital Palembang. Methods: Twenty-eight isolates collected from CRE-infected patients identified by Vitek 2 Compact (bioMerieux, USA) in dr. Mohammad Hoesin Hospital Palembang during September—November 2017. AAC(6’)-Ib gene was identified using PCR method, then visualize by electrophoresis. The result is then analyzed by comparing it with a susceptibility test. Results: Out of 28 samples, AAC(6’)-Ib is identified in 22 (78.57%) samples. Samples with AAC(6’)-Ib showed to be less resistant to various antibiotics, significantly to amikacin (p=0.023). Conclusion: AAC(6’)-Ib gene is found in most of samples implying its frequent occurrence in Indonesian patients.